TGT Penerapan Model Pembelajaran Kooperatif Tipe TGT Untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Pada Pelajaran IPAS di Kelas IV SD: Penerapan Model Pembelajaran Kooperatif Tipe TGT Untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Pada Pelajaran IPAS di Kelas IV SD - Nurkhasanah, Anna; Fajrina, Nurul; Ermayanti (UNIB Press, 2025)
This study aims to enhance the learning activities and outcomes of fourth-grade students at SDN 117 Palembang by implementing the Team Games Tournament (TGT) model. The research follows a classroom action research (PTK) approach, conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. Data collection techniques include tests, observations, and documentation at the end of each cycle. The success criteria are defined as at least 75% of students actively participating and achieving a minimum score of 75, based on the established competency standards (KKM). The findings from cycle I indicate that the average student participation rate was 69.68%, while learning completeness reached 71.42%. In cycle II, both aspects improved, with student participation rising to 79.17% and learning completeness reaching 82.14%. These results demonstrate that the TGT learning model is effective in increasing student engagement and improving learning outcomes in fourth-grade science subjects.